STRATEGI PENGELOLAAN RADIO SIARAN DI TENGAH-TENGAH PERKEMBANGAN TEKNOLOGI INTERNET - Siantari Rihartono (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
Communication Technology Advancement requires broadcast radio management to have a strategy that is able to cope with intense competition in the middle of the computer era. The presence of radio broadcasts through internet-based on-line to stimulate conventional broadcast radio had to pack to spur meet the needs of listeners. Strategies undertaken in the radio broadcasts follow the trend of technology through radio broadcasts done by conducting research to meet the needs of listeners as a basis for planning the broadcasting format, scheduling programs based segment and timeliness in order to fulfill the needs of listeners.Radio broadcasts via on line to form a new broadcast of programs with the intention to expand the global reach of the listener as konskwensi of radio broadcasting in the era of technology. Broadcast radio capability on line is able to explore the entire universe globally, then the management of broadcast radio still sought listeners if they can overcome technological determination. Broadcast radio management strategy will continue to evolve in line with advances in technology. Whatever the technological advances of communication occurs when a radio broadcast.